Perceptions of Crack Users on Their Family Relationships in Childhood and Adolescence. - Barros, Naiara Alves de (2019)
The main objective of this study was to analyze the perceptions of crack users on their family relationships in childhood and adolescence. In this qualitative study, 29 crack users of both sexes participated. Data from the semi-structured interviews were analyzed according to thematic content and organized into categories. Results show that the crack users perceive their family bonds during childhood and adolescence as fragile. In addition, they mention the experience of violence and drug use among family members. The data indicate the need to strengthen the care of family members, who often also face problems related to substance use, and the development of preventive educational activities in childhood and adolescence.